Economic governance institutions in a global political economy : implications for developing countries - Evans, Peter (UN New YorkUS, 1999)
Looks at the political tensions surrounding the actual and potential institutional role of the WTO. Considers the WTO's relationship with prior modes of economic governance (i.e. the nation state) and then the politics surrounding the possible expansion of the WTO's governance role in the future in a way that would address inequality as well as openness.